A Review on Potential of Development New Weave Pattern Design using Glass Fiber and Kenaf Fiber for Intraply Composite - Yaakob, Mohd Yuhazri (International Journal of Integrated Engineering, 2015)
Mechanical properties of the laminated composite made from fabric type reinforcement can be affected by using the method of bonding and finishing due to the constructional parameter of each lamina. Hence, the new intraply between glass fiber and kenaf fiber for composite structure is proposed toward improving overall mechanical and physical properties of intraply composite structure. Implementation of natural fiber in synthetic fiber reinforced composite has high potential to be explored scientifically. This review is mainly focused on the theory and the knowledge of composite material which found over the years by various scientists and researchers as well as related studies based on the previous researches. The types and roles of matrix and fiber materials in composites are also discussed. Major findings in this review show that the characteristics of composite depend on the weave patterns and the structure of interply and intraply. Therefore, the new intraply for glass fiber and kenaf fiber in composite structure is expected to perform better in aspect of mechanical and physical properties, besides reduced the dependency to glass fiber (100%). Finally, it will propose the most effective weave pattern designs in the functional combination form of glass and kenaf fibers. The numerical results are compared with the experimental data available in literature.